THREE MING DYNASTY MARTYRS AND THEIR MONSTROUS MOTHERS-IN-LAW. (1st September 2013) - Carlitz, Katherine
Abstract : The Ming dynasty was the first to see widespread adoption of the cult of female chastity and fidelity, with its prevalence of suicide and martyrdom. This article uses three accounts of Ming dynasty chastity-martyrdom to explore contradictions and tensions in the social expression of the cult. In these three stories, young wives die resisting pressure from their licentious mothers-in-law to engage in adulterous acts. The mothers-in-law render their daughters-in-law unable to model the filial obedience that was a central feature of Ming gender ideology. The resulting tensions are analyzed to situate the Ming chastity cult culturally, by relating it to other late imperial discourses about women, such as the surge in erotic novellas, the idealization of the courtesan, the expansion of women's devotional cults, and the increasingly irreverent tone of literati fiction.